2019
DOI: 10.1590/0034-7167-2018-0020
|View full text |Cite
|
Sign up to set email alerts
|

Social participation and personal autonomy of individuals with spinal cord injury

Abstract: Objective: To investigate, based on scientific literature, evidence on social participation and personal autonomy of individuals with spinal cord injury. Method: Integrative review of the literature including studies published between January 2006 and September 2016, obtained in the databases PubMed, CINAHL and LILACS. The guiding question was: "What evidence is available in the scientific literature about the social participation and/or personal autonomy of individuals with spinal cord injury?" The data were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
13
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 28 publications
1
13
0
8
Order By: Relevance
“…Regarding rehabilitation, the focus is shifting from a biomedical perspective to a personcentered perspective, which is included and a participant in a given society. This shift from understanding perspective to understanding it as social inequality reinforces the idea of difference, not as an individual attribute, but as a result of a society still unprepared for human diversity (1)(2)(3) . Thus, the promotion of autonomy and participation are, at the same time, fundamental criteria and central objectives of rehabilitation.…”
mentioning
confidence: 90%
See 2 more Smart Citations
“…Regarding rehabilitation, the focus is shifting from a biomedical perspective to a personcentered perspective, which is included and a participant in a given society. This shift from understanding perspective to understanding it as social inequality reinforces the idea of difference, not as an individual attribute, but as a result of a society still unprepared for human diversity (1)(2)(3) . Thus, the promotion of autonomy and participation are, at the same time, fundamental criteria and central objectives of rehabilitation.…”
mentioning
confidence: 90%
“…The terms equal opportunities, equality, overcoming barriers, accessibility and non-discrimination, are summarized as participation and inclusion in society. These are foundations inherent to human rights and represent aspects of respect and appreciation for human diversity (1) , considering the ultimate goal of rehabilitation to achieve and retain the highest possible level of autonomy for social participation (2) .Regarding rehabilitation, the focus is shifting from a biomedical perspective to a personcentered perspective, which is included and a participant in a given society. This shift from understanding perspective to understanding it as social inequality reinforces the idea of difference, not as an individual attribute, but as a result of a society still unprepared for human diversity (1)(2)(3) .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The ultimate goal of Spinal Cord Injury (SCI) rehabilitation is to restore and retain the highest possible level of autonomy in order to maximize the patients' community participation. [ 1 ] SCI is a life-threatening condition that has a significant impact on the survivors and changes their daily lives, their autonomy, and their roles in the family and society. [ 2 ] The mean prevalence of SCI is 20-50 in million per year in the world.…”
Section: Introductionmentioning
confidence: 99%
“…[ 9 ] Several studies have shown that barriers to community participation and autonomy of SCI patients are related to sociocultural conditions, SCI outcomes, attitude of the rehabilitation staff or caregivers such as overprotection or depriving the patient of social activities, architectural structures, and access to public services. [ 1 10 ]…”
Section: Introductionmentioning
confidence: 99%